Empowerment and faith: unraveling the Hui women’s mosques in China - Mai, Jianjun (IIUM Press, 2023)
ABSTRACT The Hui Muslims constitute the largest Muslim minority group in China. The Hui women’s mosques in China is a very unique phenomenon within the broader Muslim world. Emerging within a specific historical context, the Hui women’s mosques stand as a testament of the remarkable resilience of the Hui Muslims in preserving their Islamic faith and Muslim identity in a predominantly non-Muslim society heavily influenced by Confucian culture. The previous studies on Hui women’s mosques left two crucial questions unanswered: Why did Hui women’s mosque emerge exclusively in the eastern and central regions of China, and not in northwestern region where the concentration of Hui Muslims’ population is higher? Why was this phenomenon limited to the Hui Muslim community and not observed among other Muslim ethnic groups in China? This study employs historical, analytical and contexture analysis approaches to accomplish three research objectives. Firstly, it aims to re-examine the historical background of the Hui Muslims and the emergence of Hui women's mosques during the Ming and Qing dynasties within this particular ethnic group. Secondly, the study seeks to address the aforementioned questions and reidentify the possible causes for the emergence of the Hui women’s mosques in specific regions in China. Thirdly, the study intends to provide an Islamic perspective to illuminate the unique phenomenon of Hui women's mosques in China.